Contribuições de Focault a temática da gestão e subjetividades : uma análise sobre poder - Souza, Eloisio Moulin de (2004)
Critical management studies (CMS) or the critical theory in administration has been utilized by many organizational researchers. Inside the critical theory there are Marxists, neo-Marxists and Foucaultian chains. Foucaultian analysis appears in this conte